2017
DOI: 10.1111/bcpt.12857
|View full text |Cite
|
Sign up to set email alerts
|

Birth Outcome of Children Fathered by Men Treated with Systemic Corticosteroids during the Conception Period – A Cohort Study based on Nationwide Data

Abstract: Information on the safety of paternal use of medications prior to the time of conception is limited, and there is little available evidence regarding possible adverse effects of paternal use of systemic corticosteroids (SCS). In this cohort study, based on nationwide data, we examined the association between paternal use of SCS prior to conception and adverse birth outcome. The study includes data from all singletons born in Denmark from 1 January 1997 through 2013 (N = 1,013,994). Children fathered by men who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…No drug-specific information about systemic corticosteroids in the Danish data was available and both registries have no information about the used dose or indication. Larsen et al only found a higher risk of birth defects in the Danish registries, although it was not statistically significant, after one or two redeemed prescriptions ( Larsen et al , 2018 ). Smaller numbers are reported in transplantation patients ( Penn et al , 1971 ; McGeown and Nevin, 1978 ; Xu et al , 2011 ).…”
Section: Discussionmentioning
confidence: 98%
“…No drug-specific information about systemic corticosteroids in the Danish data was available and both registries have no information about the used dose or indication. Larsen et al only found a higher risk of birth defects in the Danish registries, although it was not statistically significant, after one or two redeemed prescriptions ( Larsen et al , 2018 ). Smaller numbers are reported in transplantation patients ( Penn et al , 1971 ; McGeown and Nevin, 1978 ; Xu et al , 2011 ).…”
Section: Discussionmentioning
confidence: 98%
“…During the second and third years of life, the overall risk of childhood infections was not increased after fathers' use of 5-ASA medications, thiopurines or anti-TNF-a agents. The overall risk of childhood infections during the second and third years of life was not significantly increased after fathers' use of corticosteroids.Our former Danish studies as well as a recent study by Meserve et al have shown that there is no increased risk of adverse birth outcomes of the children of fathers with IBD and other immunemediated inflammatory diseases who used thiopurines, methotrexate and biologics just prior to conception [9][10][11][12]. Winter et al found no difference in preterm birth, congenital abnormalities (CAs) or SGA in the children of fathers who used methotrexate within 3 months prior to conception 10.…”
mentioning
confidence: 56%
“…The lack of studies on preconception paternal exposure to immunosuppressive drugs and the impact on offspring health was confirmed in a recent large systematic review 6 . Only a few previous studies have been published on adverse birth outcomes (preterm birth, small for gestational age and congenital malformations), even fewer studies on long‐term outcomes, and no studies on childhood infections 9–14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of nationwide studies from Denmark regarding the safety of paternal immunosuppressive medications on short-term birth outcomes. [12][13][14][15] In these studies, paternal use of azathioprine/mercaptopurine, infliximab, adalimumab, corticosteroids and methotrexate prior to conception showed reassuring results. Also, Grosen et al [16][17][18] examined sperm integrity in men with inflammatory bowel disease via the Sperm Chromatin Structure Assay, one of the most sensitive methods for assessing sperm DNA integrity.…”
mentioning
confidence: 90%